Foreign Investment across the Belt and Road Patterns, Determinants, and Effects - Chen, Maggie Xiaoyang (The World Bank, 2018)
This paper examines the patterns and economic effects of foreign direct investment across the Belt and Road Initiative countries and assesses the potential role of the initiative in shaping the patterns and effects. Exploring cross-country bilateral transportation cost and foreign investment data, the analysis shows that, by reducing overall travel times and transportation costs, the proposed Belt and Road Initiative transportation network can pave the way for additional investments and increased growth in gross domestic product. But the magnitude of the effect varies significantly across source and destination countries. Aggregate foreign direct investment in Belt and Road Initiative countries is predicted to increase by around 5 percent, with regions such as Sub-Saharan Africa and East Asia and Pacific seeing greater potential gains. The increase in foreign direct investment can exert a positive effect on GDP, trade, and employment growth, especially for lower-income countries